Born together--reared apart : the landmark Minnesota twin study - Segal, Nancy L., 1951- (Harvard University Press, 2012)
An overview of the Minnesota Study of Twins Reared Apart, which posits that, across a number of traits, twins reared separately are as alike as those raised together--